Standerd cervical mediastinoscopy in the diagnosis of mediastinal mass in Ghazi Al-Hariri Hospital - Jaber, Sabah N.; Hussein, Abdulameer M.; Aday, Bashar B (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Mediastinoscopy is an integral part in the diagnosis of mediastinal mass. The most common indications for mediastinoscopy is for tissue sampling and determining the extent of lung cancer.Objectives: To validate our experience with standard cervical mediastinoscopy and to evaluate the usefulness of cervical mediastinoscopy in the assessing the mediastinal diseases when imaging modalities are none diagnostic.Material and Methods: A retrospective study of 16 patients between January 2012 and July 2014. Mediastinoscopy was indicated for diagnostic staging of nodal disease related to lung cancer in 8 patients (group I) and for isolated mediastinal lymphadenopathy in 8 patients (group II)Results: There were 11 males and 5 females, with a mean age of 47 years. The mean operative time was 30 minutes and the mean hospital stay was 8 hours. In lung cancer (group I) there was positive results in 3 patients and negative results in 5 patients. In patients with isolated mediastinal lymphadenopathy (group II), TB was the commonest diagnosis. There was no surgical related morbidity or mortality in our study. The sensitivity and specificity of standard cervical mediastinoscopy in this study was 100%Conclusion: Standard cervical mediastinoscopy is safe in the hands of well trained persons and needs a good knowledge of the anatomy of the region, cost effective, highly specific and still the first investigation of choice in the diagnosis of mediastinal nodal involvement.